Leiomyosarcoma after Total Laparoscopic Hysterectomy with Power Morcellation - Tsukasa Takahashi; Tomohisa Ugajin; Noriaki Imai; Atsushi Hayasaka; Nobuo Yaegashi; Takeo Otsuki (Case Reports in Obstetrics and Gynecology)
Introduction. Power morcellation is an effective and minimally invasive technique used to remove specimen tissues or the uterus in total laparoscopic hysterectomy (TLH). However, it has the risk of intraperitoneal dissemination of tissue and can cause a parasitic myoma. We report a case of leiomyosarcoma that occurred 4 years after TLH with power morcellation for fibroids. Case. A 52-year-old woman was referred to our hospital with a pelvic mass. She was diagnosed to have submucosal fibroids and had undergone TLH with power morcellation 4 years previously. The uterus weighed 398 g at that time. At present, a parasitic myoma was suspected, owing to the diagnosis of fibroids on the initial pathological evaluation. She underwent laparotomy, and the tumor was removed. Although the pathological evaluation confirmed the tumor to be a leiomyosarcoma, a review of the initial tissue did not show the presence of any malignancy. Since there was no metastasis, she was followed-up without additional treatment. Conclusion. Even if the initial pathologic evaluation suggests a benign mass, parasitic myoma and even sarcoma can occur after TLH with power morcellation. Considering the risk of dissemination and occult malignancy, the use of power morcellation should be avoided if there are alternative options to remove the tumor.